Bergmann glial GlyT1 mediates glycine uptake and release in mouse cerebellar slices - Huang, Hao (Blackwell Science Inc, 2004)
Glycine is an inhibitory neurotransmitter and is critical for NMDA receptor activation. These roles are dependent on extracellular glycine levels, which are regulated by Na(+)/Cl(−)-dependent glycine transporters (GlyTs) in neurones and glia. The glial GlyT subtype GlyT1 is well located to activate NMDA receptors. However, glial GlyTs have not been studied in an intact system thus far. Whole-cell patch-clamp recordings were obtained from Bergmann glia in mice cerebellar slices to determine whether these glia express functional GlyT1 that can mediate both glycine uptake and efflux. In the presence of a glycine receptor blocker, glycine and a substrate agonist for GlyT1, sarcosine, induced voltage-dependent inward currents that were abolished by removing external Na(+), identifying them as transport currents. Inhibitors of glycine transport through GlyT1 (sarcosine and (N-[3-(4′-fluorophenyl)-3-(4′-phenylphenoxy)propyl]sarcosine (NFPS)) reduced glycine currents by ∼85%, consistent with positive immunostaining for GlyT1 in Bergmann glia while inhibitors of glycine transport through GlyT2 (4-benzyloxy-3,5-dimethoxy-N-[1-(dimethylaminocyclopently)methyl]benzamide (ORG 25543) and amoxapine) or through systems A and ASC did not affect glycine transport currents. Following internal glycine perfusion during the recording, outward currents progressively developed at −50 mV and external glycine-induced uptake currents were reduced. Using paired recordings of a Bergmann glial cell and a granule cell in the whole cell and outside-out modes, respectively, depolarizations of Bergmann glia to +20 mV induced a 73% increase in the open probability of glycine receptor channels in membrane patches of granule cells. This increase was prevented when NFPS was included in the bath solution. Overall, these results demonstrate for the first time that Bergmann glia express functional GlyT1 that can work in reverse at near-physiological ionic and internal glycine conditions in brain slices. These glial GlyTs can probably mediate glycine efflux under conditions of metabolic impairments like ischaemia.